New E-Learning Framework Based On Patterns And Constructive Templates Using Instructional And Learning Strategies - Jegan, Thayanithy (2006)
Content development plays a key role in e-learning. Designing multimedia content for e-learning can enhance the efficiency of online teaching and learning. This thesis work proposes a new approach based on patterns and constructive templates which provides a cost effective solution to e-learning content development. A pattern based e-learning framework, which includes an authoring tool and a learning management system is presented in this thesis. This new framework facilitates delivery of e-learning content using different teaching and learning strategies.